Efforts to Develop the Capacity of MSMEs Through Business Assistance for BTPN Syariah Customers at the Pogalan Trenggalek Sharia Mobile Market - Febrianti, Fina Fajar; Nisa, Fauzatul Laily; Oktafia, Renny (Pascasarjana Universitas Mataram, 2025)
This service program focuses on empowering Micro, Small and Medium Enterprises (MSMEs) in the MMS Pogalan area by BTPN Syariah. The aim of the activity is to identify the implementation of mentoring programs, analyze supporting and inhibiting factors, and provide an impact on customer business development. The method implemented is carried out through direct training and socialization using interview techniques, using SWOT analysis to share the potential and challenges of MSMEs. Mentoring is carried out over four sessions, with each session lasting one month and four meetings. The results of the service show a significant impact on various aspects of the business. Economically, there is an increase in turnover with the expansion of the marketing reach. The managerial aspect has undergone a transformation with the ability of MSME players to carry out simple bookkeeping, separate personal and business finances, and make sustainable financial plans. Branding and marketing are developing with the creation of brand identities and the use of social media for promotions. The most basic psychological and social impact is increasing the self-confidence, motivation and adaptability of business actors. Even though it can overcome limited resources and traditional cultural barriers, the BTPN Syariah mentoring program proves that empowering MSMEs requires a comprehensive approach that goes beyond just financial assistance, covering managerial, psychological and socio-economic aspects.